(untitled) (Research, Society and Development, 2025)
This study aims to comprehensively and critically analyze the structural, economic, and legal effects of the Tax Reform implementation on the differentiated tax regime of the Manaus Free Trade Zone, considering its implications for regional productive dynamics, industrial competitiveness, and the sustainability of the development model established in Western Amazonia. The research, bibliographic in nature and qualitative in approach, examines the main changes brought about by the new tax system based on the dual VAT (IBS and CBS), as well as its compatibility with the differentiated tax regime of the Manaus Free Trade Zone. The results show that, although the Reform maintains tax incentives until 2073, uncertainties persist due to the lack of specific regulations, especially regarding the compensatory mechanisms necessary to preserve the competitiveness of the Manaus Industrial Hub. It is observed that the potential effects include risks to legal certainty, possible inequalities between industrial and commercial sectors, and uncertainties about revenue sharing. It is concluded that the effectiveness of the regime will depend on the articulation between sub-constitutional legislation, federative coordination, and public policies that ensure normative stability and continuity of regional development.